RECALL PARTISIPATIF (Paradigma Asas Musyawarah Mufakat dalam Mekanisme Pemberhentian Anggota Dewan Perwakilan Rakyat Republik Indonesia) - ISWATUL HASANAH (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract The Recall rights in Indonesia is fully given to political parties (Article 213 of Law No. 27 of 2009 on the MPR, DPR, DPD and DPRD and Article 12 letter h Law No. 2 of 2008 on Political Parties). There are several things that need to be reviewed in granting the right of recall to political parties: 1) there are no clear parameters (reasons and interests) implementation of the recall; 2) the mechanism of recall by the political party system paradigm indicates inconsistency with the sovereignty of the people that built through general elections; 3) granting the right of recall to a political party is not the principle of rule of law; 4) there is a judicial review about recall as evidence of disagreement with the recall provisions in Indonesia; 5) recall by political parties on the potential of tyranny and limiting functions of Parliament. Indonesia is not the state that has sovereignty from the people, but also embrace the democratic party in constitutional practice. Related with recall wholly given to political parties, based on the theory, the reality of law, and the state of society in Indonesia, it is not wise to erase the right of recall on political parties, but also be very discriminating when it does not involve the people in a term to control mechanism. Thus, the determination of holding such rights issues can be resolved if there is harmonization between them through participatory recall. Participatory recall an idea over legal issues with using a pre-election strategy, performance monitoring strategy, and the strategy of repressive measures, to monitoring members of the House of RepresentativesÂ  since general elections until the start of the performance period. This process will promote the use of the principle of consensus agreement. Keywords: Removal the Member of DPR RI, Â Recall Participative, The Principle of Consensus Agreement